The Varying Effects of Incarceration, Conviction, and Arrest on Wealth Outcomes among Young Adults. (25th July 2019) - Maroto, Michelle; Sykes, Bryan L
Abstract: Previous research indicates that incarceration leads to declines in rates of homeownership and net worth, especially among baby boomers, but questions remain as to how other types of criminal justice system contact affect wealth outcomes during the transition to adulthood. Using data from the 1997 National Longitudinal Survey of Youth, we investigate how arrests, convictions, and incarceration influence net worth, financial assets, and debt among young adults. We find that most contact with the criminal justice system limited the ability of young adults to accumulate wealth between the ages of 25 and 30, an especially important time for building life-cycle wealth. Arrests were associated with asset and debt declines of 52–53 percent, and incarceration led to net worth and asset declines of 34 and 76 percent, respectively. These direct effects were also bolstered by the indirect effects of these variables through their relationship with marriage and earnings, especially in the case of incarceration. This study draws attention to how criminal justice system contact affects early adult wealth, thereby setting the stage to influence a host of life course dynamics for individuals and their families.